INTERAKSI JURU PARKIR DENGAN WISATAWAN DI DAYA TARIK WISATA PANTAI KUTA, KABUPATEN BADUNG, BALI (Studi Kasus Praktek Perparkiran) - Stephani Shelpia Pratiwi; I Gst. Agung Oka Mahagangga (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2016)
This study entitled parking attendants interaction with tourists at Kuta Beach tourist attraction, Badung District, Bali. The background backs by parking rates that have been marked-up by unscrupulous parking attendants at a cost that does not match the price listed on the parking ticket. The purpose of this study is to determine the practice of parking by parking attendants at Kuta Beach tourist attraction and to understand the interaction between parking attendants with tourists in Kuta Beach tourist attraction. The method used in this study is a qualitative method. Qualitative methods referred in this study is an overview of the practice of parking in general and the practice of withdrawal of parking rates that have been marked up by parking attendants in Kuta Beach tourist attraction, Bali. From these results, it can be explained that the number of tourists who pay are not as it is printed on the tickets, in fact tourist pay higher rate than in the parking ticket. Based on the result from questioner, tourist are not satisfied with the parking attendant quality and the parking area condition. There is no real interaction between tourists and parking attendants, only when tourists want to have their bike/car out then the parking attendant asking for the money. Sometimes parking attendants didn’t show their gratitude at all to the tourists by saying thank you.